High inclination X-ray and cataclysmic binaries - Naylor, T; Timothy Naylor (1987)
﻿ An introduction is given to the fields of X-ray and cataclysmic binaries, low mass X-ray binaries (LMXBs) and globular clusters. New observations of the W Vir star AC5 (=V86) are used show that it is probably the source of Hα emission previous authors have found in core of the globular cluster M15. The first phase resolved optical spectroscopy of AC211, the optical counterpart of the X-ray source in M15, are presented, and its binary period discovered to be 9.l±0.5 hours. A re-analysis of archive ultraviolet (UV) spectra of M15, shows spectral features which are attributed to AC211. These observations are combined with those of other authors, to prove AC211 is probably an "accretion disc corona" (ADC) source. After reviewing the superoutbursts of the SU UMa class of dwarf novae, X-ray, UV, optical and infrared observations of the SU UMa star OY Car are used to show that during superoutburst there is extensive vertical structure in its accretion disc, similar to that in the ADC and "dipping" LMXBs. Archive UV data from the 1978 outburst of WZ Sge shows that it had similar vertical structure. UV observations presented of EX Hya during a bright outburst may have the same explanation. From the OY Car data, a temperature and area for the region which produces the "superhump" light are derived, of 8 OOOK and -1020cm2, respectively. It is found that during OY Car's superoutburst, the size of the 0-C variations of the eclipse timings are significantly smaller than was previously thought, and that it has an extended X-ray source whose size is comparable to the binary separation. The results are discussed with respect to models of the superhump phenomena in SU UMa stars, and possible causes of vertical disc structure in X-ray and cataclysmic binaries.